Interface facilitated transformation of voids directly into stacking fault tetrahedra. (15th April 2020) - Kong, X.F.; Gao, N.; Beyerlein, I.J.; Yao, B.N.; Zheng, S.J.; Ma, X.L.; Legut, D.; Germann, T.C.; Zhang, H.J.; Zhang, R.F.
Abstract: Voids, helium bubbles and stacking fault tetrahedra (SFTs) are common irradiation-induced defects in face-centered cubic (FCC) metals and their alloys that have detrimental effects on their deformation behavior and lifetime. The formation mechanisms of voids and SFTs have been investigated in single crystals but the potential augmentation of these mechanisms by a heterophase interface has not been well studied. Here, using transmission electron microscopy (TEM), we report on the stability of both SFTs and voids at interfaces in an irradiated Cu/Ag nanolayered composite. With atomistic simulations, we show that the heterophase interface can promote the transformation of voids (<2 nm diameter) directly into SFTs. The interfacial misfit dislocations generate an atomically varying stress field that substantially reduces the activation barrier for the transformation at an interface compared to that in a single crystal or coherent interface. The transformation mechanism involves the sequential hopping of vacancies, starting at the interface and then later progressing to the nearest and next nearest atomic layers. The calculations further show that just a few helium atoms can hinder this mechanism and stabilize interfacial voids, explaining the coexistence of voids and SFTs near the interface observed experimentally. Last, the effect of stabilized defects at the interface on dislocation nucleation is studied via atomistic calculations employing quasi-static loading schemes. The results indicate that both voids and SFTs promote interfacial dislocation nucleation, which, in turn, damages the SFTs. These findings can provide the insight needed to design strategies for healing irradiation defects by interface engineering. Graphical abstract: Image, graphical abstract